A cross-cultural comparison of the self-efficacy of middle-school mathematics teachers across Turkey and the United States. Issue 8 (14th September 2022) - Sevgi, Sevim; Berberoglu, Giray; Cobb, Paul; Smith, Thomas M.
ABSTRACT: This study aims to compare teachers' self-efficacy across Turkish and American in-service middle-school mathematics teachers. The samples consist of 379 Turkish and 245 American in-service middle-school mathematics teachers. The self-efficacy questionnaire of the Middle-school Mathematics and the Institutional Setting of Teaching (MIST) scale was used in the study. The exploratory factor analysis revealed two dimensions of the self-efficacy measures across the American and Turkish teachers, such as classroom management and student support strategies. The measurement invariance property of the scale was evaluated before comparing the means of the groups. Despite the differences between the education systems, teachers' efficacy beliefs function quite similarly across the countries. The statistically significant mean differences in the subscale scores of efficacy measures between Turkish and American samples have no practical value. In both countries, teachers reported high level of confidence in efficacy beliefs in classroom management and student support strategies.